2020
DOI: 10.1111/nph.16734
|View full text |Cite
|
Sign up to set email alerts
|

GmVTL1a is an iron transporter on the symbiosome membrane of soybean with an important role in nitrogen fixation

Abstract: Legumes establish symbiotic relationships with soil bacteria (rhizobia), housed in nodules on roots. The plant supplies carbon substrates and other nutrients to the bacteria in exchange for fixed nitrogen. The exchange occurs across a plant-derived symbiosome membrane (SM), which encloses rhizobia to form a symbiosome. Iron supplied by the plant is crucial for rhizobial enzyme nitrogenase that catalyses nitrogen fixation, but the SM iron transporter has not been identified. We use yeast complementation, real-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 75 publications
1
35
1
Order By: Relevance
“…MtVTL4 , MtVTL5 , MtVTL6 and MtVTL7 are closely related paralogues on chromosome 4 which are more similar to Arabidopsis thaliana VTL5 than to other AtVTL genes. In contrast, MtVTL8 has no direct homologue in Arabidopsis thaliana , but is closely related to SEN1 in L. japonicus (Hakoyama et al ., 2011) and NODULIN‐21 of soybean ( GmNod21 , Delauney et al ., 1990; renamed GmVTL1 in Brear et al ., 2020 and Liu et al ., 2020). The amino acid sequences of MtVTL8 and LjSEN1 share 75.7% similarity (63.0% identity).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…MtVTL4 , MtVTL5 , MtVTL6 and MtVTL7 are closely related paralogues on chromosome 4 which are more similar to Arabidopsis thaliana VTL5 than to other AtVTL genes. In contrast, MtVTL8 has no direct homologue in Arabidopsis thaliana , but is closely related to SEN1 in L. japonicus (Hakoyama et al ., 2011) and NODULIN‐21 of soybean ( GmNod21 , Delauney et al ., 1990; renamed GmVTL1 in Brear et al ., 2020 and Liu et al ., 2020). The amino acid sequences of MtVTL8 and LjSEN1 share 75.7% similarity (63.0% identity).…”
Section: Resultsmentioning
confidence: 95%
“…In particular VTL8 is critical for delivering iron to the bacteroids and for establishment of the nitrogen‐fixing bacteria. While this article was undergoing review, two studies describing a specific VTL in soybean nodule development were also accepted for publication (Brear et al ., 2020; Liu et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana , most VTL transporters localize to the tonoplast and participate in iron homeostasis [25] . Interestingly, recent studies have shown that VTL1a from Glycine max , VTL8 from Medicago truncatula, and probably SEN1 from Lotus japonicum localize to the symbiosome membrane and deliver iron from the plant to the bacteroid in order to supply iron-demands derived from the symbiosis interaction [41] , [42] , [43] , [44] .…”
Section: Ccc1/vit1 Family Structure and Functionmentioning
confidence: 99%
“…Functional studies in several legume species have shown that MATE proteins homologous to FRD3 in Arabidopsis facilitate iron transport from the nodule xylem into the nodule ( Wang et al , 2017 ; Kryvoruchko et al , 2018 ). An NRAMP homologue then transports iron into the infected cell, and VIT-like transporters export the iron into the peribacteroid space ( Brear et al , 2020 ; Liu et al , 2020 ; Walton et al , 2020 ), from where the nitrogen-fixing bacteria can take it up with as yet unknown transporters.…”
Section: Iron In Plant–microbe Interactionsmentioning
confidence: 99%